PREVENTION AS AN OBJECT OF SCIENTIFIC RESEARCH OF DOMESTIC AND FOREIGN SCIENTISTS (ON THE BASIS OF THE COMPILATION METHOD) - Трофименко, Володимир Анатолійович (Вісник НЮУ імені Ярослава Мудрого: Серія: Філософія, філософія права, політологія, соціологія, 2020)
The actual value of the topic. Ukraine is integrating more and more into the European community by transforming national legislation and changing the status of public authorities. The law enforcement system, in particular the National Police, is a litmus test for such changes because of the place it occupies in the system of public authorities and its influence on the state of public life and public order in society. Civil society is beginning to place new demands on the National Police in response to changes in the direction vector of its activities. Previously, it was a state armed body of state power, but today it is emphasized that it is the central body of executive power that serves society. The focus of militarization has been shifted to National Police functioning status in the community. This approach extends the scope of its activities towards civil, unarmed cooperation with citizens. One of the components of this area is the prevention of crime by the police authorities. Therefore, it is important to find a modern understanding of prevention, as well as to take into account the experience of scientific development by scientists from other countries. The status of recent research and publications. Prevention, as an important area of law enforcement system, is a popular subject for scientific development in Ukraine as well as in other countries (Europe, Canada, the USA, etc.). But analysis of scientific developments allows us to see the difference in scientific approaches to disclosing its content. The purpose of the publication is to show the difference in the approaches of domestic and foreign scientists to the phenomenon of preventive activity. The outline of the main material. The section provides examples of publications on crime prevention by domestic and foreign scientists. Orientation of domestic scientists towards theoretical issues is opposed pragmatic and practical problems that arise in the process of preventive activity, and that foreign scientists are trying to solve. Conclusion. The analysis of scientific publications indicates of the different attitude of domestic and foreign scientists to such phenomenon as prevention (avoiding) of crime. Domestic scientists are arguing in the theoretical field, trying to give a clear definition of prevention on the background of a small and incomplete regulatory framework for preventive activities. National science aims to develop a fully theoretical framework for understanding prevention as a function of the law enforcement system, the National Police in particular. For foreign scientists the concepts, types and functions of prevention are given as a priori. They do not pose such a large number of theoretical questions, but try to pose and recommend ways of solving practical, applied, daily problems of crime prevention. But in solving such problems, foreign scientists very often raise important theoretical problems, such as, in fact, the same fear of crime and its prevention. According to the author, the approach of foreign scientists is more correct because they put solution of practical problems of preventive activity on the first place.